One piece. Baroque Works. Vol. 20, Hiriluk's cherry blossoms - Oda, Eiichiro, 1975-; Caselman, Lance; JN Productions (San Francisco, CA : VIZ Media, LLC, 2008)
In the final showdown with the metallic King Wapol, Luffy, Sanji, and Tony Tony Chopper refuse to give up, determined to find the "One Piece" treasure that will free them all.
"First published in Japan in 1997 by Shueisha Inc, Tokyo"--Page facing t.p.
"Parental advisory. One Piece is rated T for teen and is recommended for ages 13 and up. This v. contains fantasy violence and tobacco usage"--Page facing t.p.
"This book reads from right to left"--Back cover.
"This v. contains material that was originally published in English in Shonen Jump #59-62"--Page facing t.p.
Translated from the Japanese.
Adult
Keywords: Pirates -- Comic books, strips, etc. -- Fiction; Treasure troves -- Comic books, strips, etc. -- Fiction; Buried treasure -- Comic books, strips, etc. -- Fiction; Manga; Pirates -- Comic books, strips, etc. -- Fiction; Action and adventure comics; Graphic novels